2019
DOI: 10.1098/rsif.2019.0362
|View full text |Cite
|
Sign up to set email alerts
|

Probing in-mouth texture perception with a biomimetic tongue

Abstract: An experimental biomimetic tongue-palate system has been developed to probe human in-mouth texture perception. Model tongues are made from soft elastomers patterned with fibrillar structures analogue to human filiform papillae. The palate is represented by a rigid flat plate parallel to the plane of the tongue. To probe the behavior under physiological flow conditions, deflections of model papillae are measured using a novel fluorescent imaging technique enabling sub-micrometer resolution of the displacements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
(66 reference statements)
3
18
0
Order By: Relevance
“… 37 Nevertheless, whether or not the arrangements and density of papillae influence their mechanosensing efficiency remain poorly understood. In general, a regular square grid arrangement 17 , 38 of papillae has been used as a basic model of papillae distribution in literature. However, as seen in Figure 1 , the distribution of papillae is clearly complex and irregular.…”
Section: Resultsmentioning
confidence: 99%
“… 37 Nevertheless, whether or not the arrangements and density of papillae influence their mechanosensing efficiency remain poorly understood. In general, a regular square grid arrangement 17 , 38 of papillae has been used as a basic model of papillae distribution in literature. However, as seen in Figure 1 , the distribution of papillae is clearly complex and irregular.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work [18], we have shown that deflections of an isolated elastomeric pillar submitted to a shear flow are proportional to the local shear stresses. In the context of in-mouth texture perception, we concluded that filiform papillae could act as sensitive stress sensors.…”
mentioning
confidence: 86%
“…The deflection of an isolated pillar in a viscous flow has been successfully predicted using elastohydrodynamics [13,14,18]. In biological systems, however, hairs are usually densely packed and their mechanical behavior is likely subjected to hydrodynamic interactions.…”
mentioning
confidence: 99%
See 2 more Smart Citations